1999
DOI: 10.1046/j.1365-2664.1999.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of arthropod diversity in montane wetlands: effect of altitude, habitat quality and habitat fragmentation on butterflies and grasshoppers

Abstract: Summary 0[ The patterns of arthropod diversity were investigated in 13 montane wetlands in Switzerland[ These di}ered in altitude\ management regime "cattle!grazing vs[ mowing#\ vegetation structure "index combining vegetation height and density# and degree of habitat fragmentation[ 1[ The general arthropod diversity was determined by net sampling at 09 sampling points per site[ The diversity of grasshoppers and butter~ies was measured by counting species richness at the site and species density "species richn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
2
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(152 citation statements)
references
References 25 publications
9
132
2
4
Order By: Relevance
“…None of the studied habitat types offered plenty of food all the time, a fact that supports the importance of differences in grassland usage on a local scale, if the arthropod abundance and therefore the food supply for insectivores should be optimised Wetterstein and Schmid, 1999). Noteworthy the abundance of arthropods, especially of larger individuals, was on average higher in pastures and extensively used meadows than in fallow land and intensively used meadows.…”
Section: Recommendation For Habitat Managementmentioning
confidence: 65%
See 1 more Smart Citation
“…None of the studied habitat types offered plenty of food all the time, a fact that supports the importance of differences in grassland usage on a local scale, if the arthropod abundance and therefore the food supply for insectivores should be optimised Wetterstein and Schmid, 1999). Noteworthy the abundance of arthropods, especially of larger individuals, was on average higher in pastures and extensively used meadows than in fallow land and intensively used meadows.…”
Section: Recommendation For Habitat Managementmentioning
confidence: 65%
“…However, different aspects of grassland management are mainly discussed from the view of insect conservation (e.g. Carvell, 2002;Wetterstein and Schmid, 1999;Vulliamy, 2006;Sjödin, 2007;Radlmair and Dolek, 2002). Intensive application of fertilizers and frequent mowing or heavy grazing have indeed a negative impact on many arthropod species (von Nordheim, 1992; von Wingerden et al, 1992;Benton et al, 2003) and this may have consequences also for species depending on arthropods as food (Vickery, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat fragmentation is a primary cause of biodiversity loss (Saunders et al 1991, Kruess & Tscharntke 1994, Wettstein & Schmid 1999, but fragmentation effects on biodiversity vary greatly between studies (Debinski & Holt 2000, Fahrig 2003. This is partly because a range of different processes are subsumed under the term habitat fragmentation (Fahrig 2003, Lindenmayer & Fischer 2007.…”
Section: Introductionmentioning
confidence: 99%
“…A Swiss study found that although grazing was an effective management tool for limiting succession, (i.e., slowing the conversion of open grassland to shrubland or woodland) responses to grazing varied greatly among butterfl y species. 9 The authors suggest that any management regime be attentive to historical and species-specifi c characteristics of the species at the site, and that a diversity of management techniques be used on a regional scale in order to preserve the greatest diversity of insect pollinator habitat.…”
Section: Grazingmentioning
confidence: 99%